What is quantum computation? - Ekert, A; Hayden, P; Inamori, H; Oi, D (2001)
"Information is physical and any processing of information is always performed by physical means," an innocent-sounding statement, but its consequences are profound. When quantum effects become important, for example, at the level of single atoms and photons, the classical theory of computation becomes fundamentally inadequate. Entirely new modes of computation and information processing become possible. In the last few years there has been an explosion of theoretical and experimental research in quantum computation. In this brief review we describe some of these developments.